Aplicación de Estrategias de diseño gráfico e Industrial a una Propuesta de Material Didáctico, Comunicacional con su Respectivo Packaging, como Parte del Proyecto de los Juegos Tradicionales y Autóctonos, Impulsado por el Ministerio del Deporte para la Región Sierra - Aguilera Rojas, Christian Paúl (2014)
At some point, in every part of the Ecuadorian Sierra people has played typical games like rayuela, jump the rope or trompo; sadly times changed globalization, industrialization, science progress and new technologies make people think different about their traditional games, for this reason now is very difficult to see young people and their families remembering this games. Nowadays, people spend most of their time playing video games o just watching how others play, this propitiates sedentary habits and makes people forget about traditional games and customs of ages past provoking behavior changes, also socio-cultural habits and habilities changes. This project intends to rescue the main traditional games of the Ecuadorian Sierra based on graphic and industrial design, specifically with an illustrated book that shows how the games are played in a friendly and simple way.